Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (The MIT Press, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics–one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

L’économie politique du sexe : transactions sur les femmes et systèmes de sexe/genre - Rubin, Gayle (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 1998)
La littérature sur les femmes — tant féministe qu’antiféministe — est une longue rumination quant à la nature et à la genèse de leur oppression et de leur subordination sociale. La question n’est pas sans importance, car les réponses qui lui sont données déterminent la manière dont nous envisageons l’avenir et si nous jugeons réaliste ou non d’espérer une société égalitaire entre les sexes. Plus important, l’analyse des causes de l’oppression des femmes fonde toute estimation de ce qu’il faudrait exactement changer pour réaliser une société sans hiérarchie de genre
Première publication: 1975 http://journals.openedition.org/cedref/171
Keywords: 1900-1999; 1960-1969; 1970-1979; anthropologie; approches et analyses; capitalisme; classe ouvrière; cours; discipline; europe; famille; fem1000; france; féminisme matérialiste; histoire et politique; inégalités; marxisme; patriarcat; premier cycle; psychanalyse; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences; sciences humaines; soc1016; soc2014; sociologie; systèmes d'oppressions; thématiques; théories féministes